2015
DOI: 10.1007/s00125-015-3641-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of long non-coding RNAs in beta cell failure at the onset of type 1 diabetes in NOD mice

Abstract: Aims/hypothesis Exposure of pancreatic beta cells to cytokines released by islet-infiltrating immune cells induces alterations in gene expression, leading to impaired insulin secretion and apoptosis in the initial phases of type 1 diabetes. Long non-coding RNAs (lncRNAs) are a new class of transcripts participating in the development of many diseases. As little is known about their role in insulin-secreting cells, this study aimed to evaluate their contribution to beta cell dysfunction. Methods The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…To date, however, studies are limited with respect to the expression and function of lncRNAs in the β-cell. A recent study in mouse β-cell-derived cell lines and NOD mouse islets showed that lncRNAs 1-4 are strongly upregulated in response to proinflammatory cytokines and disease progression, respectively [75]. Carter et al [76] showed that in humans, the lncRNA GAS5 was negatively correlated with the prevalence of type 2 diabetes in a Veteran’s Administration cohort.…”
Section: Non-coding Rnas As Circulating Biomarkers Of β-Cell Stress Imentioning
confidence: 99%
“…To date, however, studies are limited with respect to the expression and function of lncRNAs in the β-cell. A recent study in mouse β-cell-derived cell lines and NOD mouse islets showed that lncRNAs 1-4 are strongly upregulated in response to proinflammatory cytokines and disease progression, respectively [75]. Carter et al [76] showed that in humans, the lncRNA GAS5 was negatively correlated with the prevalence of type 2 diabetes in a Veteran’s Administration cohort.…”
Section: Non-coding Rnas As Circulating Biomarkers Of β-Cell Stress Imentioning
confidence: 99%
“…Although it has recently been revealed that lncRNAs are associated with the progression of DM (17), no lncRNA of mitochondrial origin has been identified that is associated with DM or its complications. It is well-documented that mitochondria maintain ROS levels; high levels of ROS induce dysfunction of mitochondria, which in turn produce ROS at a higher rate (18).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of experiments and studies have performed and found the dysregulated lncRNAs profiles of various diseases in mouse models [2830]. However, an important different feature between lncRNAs and protein-coding genes are in the evolutionary conservation [10, 31].…”
Section: Discussionmentioning
confidence: 99%